2013
DOI: 10.1111/jocn.12499
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of discharge planning on the knowledge, clinical symptoms and hospitalisation frequency of persons with schizophrenia: a longitudinal study in two hospitals in Tehran, Iran

Abstract: Due to high frequency of relapse, rehospitalisation and high remedial costs of persons with schizophrenia, it is important to consider discharge planning as a therapeutic approach for patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 20 publications
0
32
0
1
Order By: Relevance
“…Khaleghparast et al [5] stated that the hospital discharge process poses a stressful time for the patients and their families. Treatment compliance improves if careful discharge planning and post discharge treatment are in place.…”
Section: Model Shift 3: 1996-2015mentioning
confidence: 99%
See 4 more Smart Citations
“…Khaleghparast et al [5] stated that the hospital discharge process poses a stressful time for the patients and their families. Treatment compliance improves if careful discharge planning and post discharge treatment are in place.…”
Section: Model Shift 3: 1996-2015mentioning
confidence: 99%
“…Previous findings suggested that the readmission rates of patients diagnosed were very high, possibly reaching 67%. Low patient knowledge regarding treatment was identified as being to blame (Khaleghparast et al [5]). Examining the effectiveness of discharge planning on the knowledge, clinical symptoms, and rates of re-hospitalization in schizophrenia patients identified appropriate discharge planning to be effective in improving patient's and caregiver's knowledge (Khaleghparast et al [5]).…”
Section: Model Shift 3: 1996-2015mentioning
confidence: 99%
See 3 more Smart Citations